The impact of 45S5 bioglass vs. β-TCP nanoparticles ratio on rheological behavior of formulated printing inks and 3D printed polycaprolactone-based scaffolds final properties - Mansure Kazemi; Hasti Esmaeili; Mansoureh Khandaei Dastjerdi; Farshad Amiri; Mehdi Mehdikhani; Mohammad Rafienia (Heliyon)
Extrusion based 3-D printing has been extensively applied to create geometrically complex composite polymer-ceramic structures as bone tissue substitute. The rheological features of the formulated bioink that regulate the printability and resolution of the printed scaffolds, rely on physicochemical properties of ink components, mainly their composition and chemical structure. The aim of this study was to evaluate the effect of different content of 45S5 bioglass (BG) and β-tricalcium phosphate (β-TCP) nanoparticles on the rheological behavior of printing inks and final composite scaffolds based on polycaprolactone (PCL)/BG/β-TCP. Ceramic nano-powders were first characterized and the composite bioinks were prepared by mixing various ratios of BG and β-TCP powders into the 50 % w/v of PCL solution (β-TCP/BG: 70/30, 50/50, 30/70, and 10/90 w/w %). All formulated inks showed a thixotropic behavior and viscosity significantly increased by applying higher fraction of BG. Interestingly highly loaded β-TCP ink (β-TCP/BG: 70/30) revealed a rubbery nature with high surface tension which reduced final scaffolds resolution. All printed scaffolds possessed highly porous structure with interconnected pores. However, porosity percentage and shape stability improved by increasing BG content which was accompanied with lower mechanical strength and superior biodegradation and bioactivity of scaffolds. The biological performance of the printed scaffolds was evaluated using osteoblast cell line MG-63. MTT assay and cell attachment observation by SEM confirmed that printed scaffolds are well biocompatible and properly support cell colonization and proliferation. In overall, besides more appropriate materialistic properties, scaffolds with β-TCP/BG: 30/70 composition provided the most favorable microenvironment for cell colonization and growth.